Determinants of Early Post-Natal Care Utilization in Madhesh Province: A Population-Based Analysis of NDHS 2020 (Voice of Teacher, 2024)
This paper focuses on post-natal care (PNC) is important in the prevention of maternal and newborn complications with timely care service received within 48 hours. Nevertheless, there is still an unequal use in low- and middle-income countries. It is estimated that socio-demographic and economic factors of early PNC uptake in Madhesh Province, Nepal. A cross-sectional design and a multistage sampling were used using nationally representative data of the 2022 Nepal Demographic and Health Survey (NDHS). There were 734 women in the sample to be analyzed descriptively and 594 to be the subjects of logistic regression. Multivariate models that were tested investigated predictors of PNC receipt in the two postnatal days. Only secondary data used and descriptive results indicated significant differences according to age, parity, education, residence, caste/ethnicity, and wealth. Logistic regression showed that the increase in probability of early PNC as a result of higher education and household wealth was large whereas women with third or higher-order births had dramatically lower chances. The effects of residence and caste decreased after adjusting, which argued that socio-economic mediation existed. The use of PNC is still unequal with more disadvantaged women (poorer, less educated, rural, and high parity) being left out. Intervention measures should be directed, pro-poor, and equity based in order to enhance access and minimize the number of maternal and neonatal deaths that can be prevented in Nepal.